PENGARUH PERSEPSI, MOTIVASI, LINGKUNGAN KELUARGA, DAN TINGKAT PENGETAHUAN TERHADAP MINAT UNTUK BERKARIR DI BIDANG START-UP - Nurhayati, Agustina; Noermijati, Noermijati (Jurnal Kewirausahaan dan Inovasi, 2022)
The development of technology and information and an increase in the number of start-up companies in Indonesia have opened the opportunity for millennials to make contributions in enhancing the human resource of companies. nevertheless, there are internal and external factors that influence their decisions to have a career in start-up area. the objective of this research is to identify the effect of perception, motivation, family environment, and level of knowledge on the intention students of Faculty of Economics and Business of Universitas Brawijaya to have a career in start-up area. The samples of this explanatory research were selected using proportionate random sampling technique, resulting in 351 respondents. Multiple linear regression were used and have led to findings that perception, motivation, family environment, and level of knowledge have significant effects on the intention to have a career in start-up area.